Risk-Taking under Limited Liability: Quantifying the Role of Motivated Beliefs - Ciril Bosch-Rosa; Daniel Gietl; Frank Heinemann (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper investigates whether limited liability and moral hazard affect risk-taking through motivated beliefs. On the one hand, limited liability pushes investors towards taking excessive risks. On the other, such excesses make it hard for investors to maintain a positive self-image when moral hazard is present. Using a novel experimental design, we show that subjects form motivated beliefs to self-justify their excessive risk-taking. For the same investment opportunity, subjects invest more and are significantly more optimistic about the success of the investment if their failure can harm others. We show that more than one third of the investment increase under limited liability can be explained through motivated beliefs. Moreover, using a treatment with limited liability but no moral hazard, we show that motivated beliefs are formed subconsciously and can lead to the paradoxical result of investors taking larger risks when their investment can harm a third party than when it cannot. These results underscore the importance of motivated beliefs in regulatory policy as they show that one should target not only bad incentives but also “bad beliefs.”
Keywords: C91; D84; G11; G41; 330